Relations between postdivorce custody arrangements, family contexts, and children's adjustment. Issue 1 (2nd January 2017) - Drapeau, Sylvie; Baude, Amandine; Ouellet, Jerôme; Godbout, Elisabeth; Ivers, Hans; Saint-Jacques, Marie-Christine
ABSTRACT: The goal of the present study was to shed light on the relation between postseparation custody arrangements and family contexts in which school-age children (8–12 years old) live so as to better understand the processes underlying their adjustment. The sample was composed of 112 dyads (parents and children) from families in joint custody ( n  = 37) or maternal custody ( n  = 75). The dyads were met with twice at a 1-year interval. Compared with those in joint custody, the respondents with sole custody had a negative opinion of the transitions between homes and had the impression that the children were more involved in interparental conflicts. This analysis showed that the difficult nature of transitions between homes was a crucial mediating variable in the relation between conflicts and the children's adjustment, but that other variables, such as the relational problems with the mother, played a role, particularly in joint custody situations.